Analisis Penyebab Terjadinya Kebocoran Kondensor pada Mesin Pendingin Ruangan di MV.Federal Oak - Bima Wardana; Andy Wahyu Hermanto; Anicitus Agung Nugroho (JURNAL BARTEK, 2025)
The air conditioning system in a room monitors the regulation of humidity and air temperature, with a focus on providing optimal levels of comfort for the ship's crew, thereby reducing fatigue and helping to improve fitness. Problems can arise and the vessel can be disrupted if maintenance schedules are not followed. Based on the researcher's experience during sea practice for 12 months on an MV ship. Federal Oak. When the ship entered summer and entered Mexico, the condenser leaked in the air conditioning engine, which disturbed the comfort of the ship's crew while working. This research aims to identify the causes, consequences, and solutions for condenser leaks in air conditioning systems. This research uses a qualitative description approach that uses Fishbone data analysis to organize and identify the factors that cause certain effects, then separate the root causes of the problem. This study found that deposits in the condenser pipe and air in the condenser are the causes of AC machine condenser leaks, dirty cooling water results in a decrease in the amount of freon that is condensed, and lack of maintenance and supervision will worsen the condition of the components. The impact of a condenser leak in an air conditioning machine is that room temperature cannot be reached because the freon, which should be converted into a liquid when it enters the condenser, actually experiences a shortage due to a leak that occurs in the condenser and a decrease in engine performance. Efforts to overcome leaks in air conditioning machine condensers include using a brush to clean dirt stuck to the capillary pipes and spraying water into the condenser pipes. Turn off the air conditioning machine and weld pipe joints that are leaking. Clean the condenser tube using a long iron. Carry out maintenance in accordance with the Plan Maintenance System.